Fenomena Yang Terjadi Pada Pasangan Suami dan Istri dalam Ketahanan Keluarga - Ria Hayati; Dirgam Ode Adulama (IAIN TERNATE, 2022)
This study examines the problems that are born in the family and how married couples respond to them. The size of the family problems that are born, should be resolved wisely and correctly. The purpose of this study is to learn about cases born into families, then provide a solution in overcoming and anticipating existing problems, in order to maintain family resilience. The process of collecting data is carried out by studying literature, in this case tracing the literature of books, scientific journals, and other reputable research results. The results found, at least three common cases were found, including divorce cases, domestic violence cases and broken home cases. From the existing cases, it can be said that domestic violence cases often occur in families. One alternative in solving family problems is to visit a counseling service center.